Remote sensing-based spatiotemporal dynamics of agricultural drought on Prince Edward Island using Google Earth engine - Fatima Imtiaz; Aitazaz A. Farooque; Gurjit S. Randhawa; Seyyed Ebrahim Hashemi Garmdareh; Xiuquan Wang; Travis J. Esau; Bishnu Acharya; Rehan Sadiq (Ecological Informatics)
Climate change is a primary factor contributing to widespread drought conditions worldwide. Therefore, assessing agricultural drought's spatial and temporal extent is crucial. This study explicitly applies remote sensing techniques to monitor drought in the cropland area of Prince Edward Island, Canada, with a particular emphasis on potato crops. The long-term drought was evaluated using MODIS for 2012–2022, while the seasonal drought at the field scale was calculated using Landsat-8 OLI/TIRS for the 2021 and 2022 crop growth seasons. The computed remote sensing drought indices include Vegetation Condition Index (VCI), Vegetation Health Index (VHI), and Temperature Condition Index (TCI), which are derived using the Google Earth Engine platform. Examining long-term drought by MODIS revealed that 2020 was the most dominant drought year, according to all three drought indices. However, the seasonal variations of VCI, TCI, and VHI at the field scale observed in the three fields in 2021 and 2022 demonstrated that June went through considerable drought in both years. August was the second critical month following June for drought conditions. CHIRPS data indicated significant rainfall anomalies relative to the long-term seasonal average for the 2021 crop season, specifically in June (−38.5 %) and August (−38.2 %), while the rainfall in the crop season in 2022 exceeded the seasonal average. Based on Pearson correlation analysis, VHI correlated strongly with VCI (CC = 0.87 for 2021 and 0.93 for 2022) and moderately with rainfall (CC = 0.68 for 2021 and 0.63 for 2022). The spatial autocorrelation analysis revealed substantial positive autocorrelation of drought for 2019, 2020, 2021 and 2022. However, 2020 has the highest spatial autocorrelation, with Moran's I of 0.54 and a z-score of 24.8. Hence, this study will optimize irrigation, decrease crop loss, sustain crop yields, and enhance food security.